Concomitant leadless pacemaker implantation and lead extraction during an active infection. (21st February 2020) - Chang, David; Gabriels, James K.; Soo Kim, Beom; Ismail, Haisam; Willner, Jonathan; Beldner, Stuart J.; John, Roy M.; Epstein, Laurence M.
Abstract: Introduction: The need for transvenous lead extractions due to cardiac implantable electronic device (CIED)‐related infections continues to rise. Current guidelines recommend complete device removal in the setting of an active infection, which can be challenging in pacemaker‐dependent patients. Methods: We retrospectively reviewed all leadless pacemaker implants between January 2018 and November 2019 and identified a subset of patients who had undergone a concomitant CIED extraction in the setting of an active infection. Baseline characteristics, procedural details, and clinical follow‐ups were recorded. Results: Seventeen patients received a leadless pacemaker during the same procedure as the CIED extraction. There were no procedural complications. All patients were being treated for an active CIED infection at the time of the procedure. Fourteen patients (82.4%) were completely pacemaker‐dependent and four patients (23.5%) had positive blood cultures at the time of the leadless pacemaker implantation. During a median follow‐up of 143 days (interquartile range: 57, 181 days), there were no recurrent infections. Conclusion: Simultaneous leadless pacemaker implantation and CIED extraction are safe and feasible in the setting of an active infection. This strategy may be particularly useful in patients that are pacemaker‐dependent.